2012
DOI: 10.4093/dmj.2012.36.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia Is a Serious Complication and Becoming an Economic Burden in Diabetes

Abstract: BackgroundThe prevalence of hypoglycemia is increasing due to the growing incidence of diabetes and the latest strict guidelines for glycated hemoglobin (HbA1c) levels under 7%. This study examined the clinical characteristics, causal factors, and medical costs of severely hypoglycemic patients in an emergency room (ER) of Uijeongbu St. Mary's Hospital.MethodsThe study consisted of a retrospective analysis of the characteristics, risk factors, and medical costs of 320 severely hypoglycemic patients with diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 12 publications
1
38
1
2
Order By: Relevance
“…In a Korean report conducted in 2012, the mean age of hypoglycemic patients was 69.5 years, which is comparable with the current study (age, 70.5 years) (1). In the present study, the mean age of the group of hypoglycemic patients with concurrent infection was 72.7 years, which was five years older than patients without infection (7,8).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In a Korean report conducted in 2012, the mean age of hypoglycemic patients was 69.5 years, which is comparable with the current study (age, 70.5 years) (1). In the present study, the mean age of the group of hypoglycemic patients with concurrent infection was 72.7 years, which was five years older than patients without infection (7,8).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, in concurrent UTI patients, missed meals exerted a reduced effect. Impaired renal function and hepatic diseases are comorbidities that are associated with hypoglycemia (1,3). In the current study, 62.4% of the hypoglycemic patients had impaired renal function and 26.3% of patients had ARF at the time of the hypoglycemic episode.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…8 A Korean study reported costs ranging from $135.50 to $1,391.00 per episode of severe hypoglycemia. 9 Swedish studies report the direct costs of hypoglycemia per patient being $12.90 for a 1-month period, while the indirect costs are $14.10 for a 1-month period, with the total cost (in base case) of hypoglycemia in Sweden being approximately €4,250,000 (~$5.74 million) per year. 10,11 In addition to an increase in health care utilization and costs, hypoglycemia also leads to decline in the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of hypoglycemia occurs in patients with chronic renal impairment and the elderly. And the most common causal factors were poor nutrition or a missed meal (7). Hence, it is appropriate that glyburide be avoided in these population groups.…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 99%